The severe adverse reaction to vitamin k1 injection is anaphylactoid reaction but not anaphylaxis. - Yan-Ni Mi; Na-Na Ping; Xue Xiao; Yan-Bing Zhu; Jing Liu; Yong-Xiao Cao (PLoS ONE)
The severe adverse reaction to vitamin K1 injection is always remarkable and is thought to result from anaphylaxis. Paradoxically, however, some patients administered vitamin K1 injection for the first time have adverse reactions. Using beagle dogs, the present study tested the hypothesis that the response to vitamin K1 is an anaphylactoid reaction. The results showed that serious anaphylaxis-like symptoms appeared in beagle dogs after the administration of vitamin K1 injection for the first time. The plasma histamine concentration increased, and blood pressure decreased sharply. After sensitization, dogs were challenged with vitamin K1 injection and displayed the same degree of symptoms as prior to sensitization. However, when the vitamin K1 injection-sensitized dogs were challenged with a vitamin K1-fat emulsion without solubilizers such asTween-80, the abnormal reactions did not occur. Furthermore, there was no significant change in the plasma immunoglobulin E concentration after vitamin K1 challenge. Following treatment with vitamin K1 injection, the release of histamine and β-hexosaminidase by rat basophilic leukemia-2H3 cells as well as the rate of apoptosis increased. The Tween-80 group displayed results similar to those observed following vitamin K1 injection in vivo. However, the dogs in the vitamin K1-fat emulsion group did not display any abnormal behavior or significant change in plasma histamine. Additionally, degranulation and apoptosis did not occur in rat basophilic leukemia-2H3 cells. Our results indicate that the adverse reaction induced by vitamin K1 injection is an anaphylactoid reaction, not anaphylaxis. Vitamin K1 injection induces the release of inflammatory factors via a non-IgE-mediated immune pathway, for which the trigger may be the solubilizer.